(untitled) (Revista Iberoamericana de Estudios Municipales, 2021)
The Integrated Urban Solid Waste Management (IUSWM) model has gained prominence in recent years in Argentina due to its social, economic, and environmental implications. Although the IUSWM model has been formally adopted, the results of the different Argentine municipalities are uneven. Based on the theory of social innovation, this work seeks to explain how and under what conditions six Argentine municipalities achieved progress in their waste management. The results show that there are two sources of innovation: entrepreneurship and social mobilization. In addition, three other factors that shape the innovation process are identified: the existence of an innovative environment, available economic resources, and coalitions between state and social actors.